Global Tn‐seq analysis of carbohydrate utilization and vertebrate infectivity of Borrelia burgdorferi. Issue 6 (15th July 2016) - Troy, Erin B.; Lin, Tao; Gao, Lihui; Lazinski, David W.; Lundt, Maureen; Camilli, Andrew; Norris, Steven J.; Hu, Linden T.
Summary: Borrelia burgdorferi maintains a complex life cycle between tick and vertebrate hosts. Although some genes have been identified as contributing to bacterial adaptation in the different hosts, the list is incomplete. In this manuscript, we report the first use of transposon mutagenesis combined with high‐throughput sequencing (Tn‐seq) in B. burgdorferi . We utilize the technique to investigate mechanisms of carbohydrate utilization in B. burgdorferi and the role of carbohydrate metabolism during mouse infection. We performed genetic fitness analyses to identify genes encoding factors contributing to growth on glucose, maltose, mannose, trehalose and N ‐acetyl‐glucosamine. We obtained insight into the potential functions of proteins predicted to be involved in carbohydrate utilization and identified additional factors previously unrecognized as contributing to the metabolism of the tested carbohydrates. Strong phenotypes were observed for the putative carbohydrate phosphotransferase transporters BB0408 and BBB29 as well as the response regulator Rrp1. We further validated Tn‐seq for use in mouse studies and were able to correctly identify known infectivity factors as well as additional transporters and genes on lp54 that may contribute to optimal mouse infection. As such, this study establishes Tn‐seq as a powerful method for both in vitro and in vivo studies of B. burgdorferi . Abstract : This work establishes Tn‐seq as a new tool for performing high‐throughput genetic fitness analyses in Borrelia burgdorferi . We used the technique to perform an in vitro screen exploring mechanisms of mannose, maltose, trehalose and N ‐acetyl‐glucosamine metabolism in B. burgdorferi as well as a complementing in vivo screen in mice. In doing so we obtained insight into the potential functions of genes annotated as encoding carbohydrate transporters and an additional function of the response regulator Rrp1.